2020
DOI: 10.1016/j.medcle.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Emotional impact of the Covid-19 pandemic on healthcare workers in one of the most important infection outbreaks in Europe

Abstract: Background and objectives The Covid-19 pandemic has put healthcare professionals around the world in an unprecedented challenge. This may cause some emotional difficulties and mental health problems. The aim of the present study was to analyze the emotional status among the health care workers form the Hospital of Igualada (Barcelona), while they were facing with Covid-19 in one of the most affected regions in all of Europe. Patients and methods A total of 395 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
58
0
13

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 23 publications
11
58
0
13
Order By: Relevance
“…In our results, the variables "female" and "nurse" showed a greater level of anxiety, just as other in studies conducted in healthcare worker populations [2, 17,18,[22][23][24]. In this sense, we should be cautious when making conclusions in this respect, as 77% of the sample was composed of women; however, these results coincide with a previous prevalence study on anxiety and depression in the Spanish population, where women obtained greater percentages than men in all anxiety-related disorders (7.6% as compared to 2.6%) [25].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our results, the variables "female" and "nurse" showed a greater level of anxiety, just as other in studies conducted in healthcare worker populations [2, 17,18,[22][23][24]. In this sense, we should be cautious when making conclusions in this respect, as 77% of the sample was composed of women; however, these results coincide with a previous prevalence study on anxiety and depression in the Spanish population, where women obtained greater percentages than men in all anxiety-related disorders (7.6% as compared to 2.6%) [25].…”
Section: Discussionsupporting
confidence: 89%
“…The degree of anxiety in the general sample in our study (56.5%) was similar to that found in Spanish healthcare workers during the COVID pandemic (58.6%) [17], although lower than that found in a study in Barcelona, where 71.6% showed anxiety symptoms [18], and higher than another study conducted in the autonomous communities of the Basque Country and Navarra, where 37% showed anxiety symptoms [2]. In both cases, the differences could be related, as the data collection was conducted during the first months of the pandemic (March/April and April, respectively), while in our case, it was conducted at the end of the State of Alarm in June.…”
Section: Discussionsupporting
confidence: 81%
“…In a study during the H1N1 outbreak, hospital staff who were in their 20's had greater anxiety about becoming infected than did older staff ( 103 ). During COVID-19, HCW who were younger were more likely to experience higher levels of post-traumatic stress symptoms, depression, anxiety, and acute stress compared to older HCW ( 23 , 26 28 , 30 , 32 , 42 , 49 , 54 , 55 , 57 , 61 , 65 , 71 , 75 , 78 , 89 , 90 , 117 , 118 , 121 , 123 , 127 , 131 , 149 , 153 , 154 ). In contrast, eight studies conducted during COVID found that HCW who were older were at greater risk of experiencing higher levels of psychological distress ( 40 , 66 , 86 , 95 , 102 , 114 , 122 , 132 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, two studies of HCW during the SARS outbreak found that HCW who were single were 1.4 times more likely to experience psychological distress than married HCW (41), and more likely to have sever depressive symptoms 3 years later (92). Similarly, HCW during the COVID-19 outbreak who were single experienced higher levels of distress than those who were married (54,57,66,69,111,122,126). Conversely, four studies conducted during COVID-19 found that being married was a risk factor for greater distress (66,75,89,94), and two studies found that married HCW with children reported greater stress than single HCW or those who were married without children (72,83).…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…Working days have been lost with obvious effects on patient care. Some have been affected by COVID infection nonetheless [ 35 , 36 ] and have experienced the potentially devastating effects of the virus on themselves and their families first hand [ 37 ]. This has also had effects on healthcare systems, which have had to cope with less than 100% of the workforce available at any one time.…”
mentioning
confidence: 99%